2017
DOI: 10.1002/mp.12554
|View full text |Cite
|
Sign up to set email alerts
|

A method for characterizing and matching CT image quality across CT scanners from different manufacturers

Abstract: Matching image appearance in terms of resolution, noise magnitude, and noise texture provides a quantitative and reproducible strategy to improve consistency in image quality among different CT scanners and reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…and Winslow et al . compared kernels on Siemens and GE 37 , 38 . Both found that the GE standard kernel was the closest match to the B31f or B31s kernel on Siemens, which agrees with our controlled protocol.…”
Section: Discussionmentioning
confidence: 99%
“…and Winslow et al . compared kernels on Siemens and GE 37 , 38 . Both found that the GE standard kernel was the closest match to the B31f or B31s kernel on Siemens, which agrees with our controlled protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Kernels could be matched across scanners from different manufacturers to achieve similar noise texture based on noise power spectrum (NPS) analysis similar to that described in this report . This matching can be expanded to include resolution (TTF) and noise magnitude as well, while at the same time meeting constraints in the dose level of the examination . This method relies on the f A and f 50 metrics of noise and resolution that are described in Sections 2.B and 2.C of this summary paper, respectively.…”
Section: Clinical Utility and Future Extensionsmentioning
confidence: 99%
“…Phantom studies can help match image appearance and thus identify comparable imaging settings across different vendors’ scanners, scanning techniques and parameters, etc. ( 68 , 69 ). For example, by analyzing noise power spectrum (NPS), a group of medical physicists conducted a study using the ACR CT phantom to quantitatively compare noise texture between two CT systems, GE and Siemens ( 68 ).…”
Section: Image Acquisitionmentioning
confidence: 99%